Hematological indicators and activity of transaminases in the blood serum of farrow sows depending on the microclimate of the premises - А. І. DМYТRОTSA (Передгірне та гірське землеробство і тваринництво)
A number of scientific studies have established that during the farrow period sows are particularly sensitive to the action of various stress factors, including housing conditions, which lead to a violation of the activity of the antioxidant status system in their body and the occurrence of oxidative stress. Therefore, maintaining the optimal parameters of the microclimate in the premises where animals are kept during this period is important factor of the proper course of metabolism in the body of sows, fetuses and in the entire farrow process.